PERANCANGAN MODEL KNOWLEDGE MANAGEMENT SYSTEM BERBASIS WEB - Ika Yuniva (LPPM Universitas Bina Sarana Informatika, 2016)
Bina Potential Rifa is a foundation in the field of education. This study discusses the model of knowledge management system at Yayasan Bina Potential Rifa Tangerang to assist the teaching staff and employees in terms of knowledge transfer. The purpose of this study to find the form of a model of knowledge management systems based on information technology by using the Joomla open source tools. This study uses a framework of amrit Tiwana, to gain knowledge management analysis. Formation of knowledge using SECI model Nonaka, after the model of knowledge management formed, the subsequent architectural design knowledge management architecture using Tiwana. In knowledge management combines the tacit knowledge and explicit knowledge among the teaching staff and employees, so it can be used to improve the performance of human resources. The results of this research are knowledge management model appropriate to enhance the performance of human resources Yayasan Bina Potential Rifa and any human resources can take the knowledge from this knowledge management system.